Analysis of codon usage bias of lumpy skin disease virus causing livestock infection - Rahman, Siddiq Ur; Rehman, Hassan Ur; Rahman, Inayat Ur; Rauf, Abdur; Alshammari, Abdulrahman; Alharbi, Metab; Haq, Noor ul; Suleria, Hafiz Ansar Rasul; Raza, Sayed Haidar Abbas (Frontiers in Veterinary Science, 2022)
Lumpy skin disease virus (LSDV) causes lumpy skin disease (LSD), is a double-stranded DNA virus that belongs to the genus Capripoxvirus of the family Poxviridae. LSDV is an important poxvirus with a world-wide distribution. It poses serious health risks to the host and has a considerable negative socioeconomic impact. Previous studies have explained the population structure of LSDV within the evolutionary time scale and adaptive evolution. However, it is still unknown how synonymous codons are used by LSDV. Here, we used 53 LSDV strains, applying the codon usage bias (CUB). Both base content and relative synonymous codon usage (RSCU) analysis revealed that AT-ended codons were more frequently used in the genome of LSDV. Further low codon usage bias was observed from the effective number of codons (ENC) value. The neutrality plot analysis suggested the dominant factor of natural selection was involved in the structuring of CUB in LSDV. Further analysis showed that LSDV has adapted host-specific codon usage patterns to sustain successful replication and transmission chains within hosts (Bos taurus and Homo sapiens). Generally, both natural selection and mutational pressure have an impact on the codon usage patterns of the protein-coding genes in LSDV. This study is important because it characterized the codon usage pattern in the LSDV genomes and provided the necessary data for a basic evolutionary study on them.